People analytics and algorithmic discrimination in selection processes - Ginès i Fabrellas, Anna (LABOS Revista de Derecho del Trabajo y Protección Social, 2024)
The use of artificial intelligence systems to adopt automated decisions, which started in the field of platform work, has extended to selection and hiring processes. Many companies and job search portals incorporate people analytics techniques to adopt automated selection and hiring decisions. Although artificial intelligence systems can greatly simplify these processes, they can also generate risks for peoples’ fundamental rights, including situations of discrimination due to the existence of biases in these systems. This article analyses the use of people analytics and automated decision systems in the field of selection and hiring of people, to identify the existence of biases in the use of this technology and determine the challenges it poses to its legal treatment.